The Contribution of Graduate of Riga Polytechnicum Alfons Eihvalds (1862–1923) to the Development of the Tukums Town - Ozola, Agrita (History of Engineering Sciences and Institutions of Higher Education, 2020)
The article is the first comprehensive study on businessman, bank employee, Mayor of the Tukums town municipality (1907–1915; 1918–1920) and public employee Alfons Eihvalds. It reflects the life of A. Eihvalds at the end of the 19th century / beginning of the 20th century, his role in the management of Tukums town, its economic and social life – Tukums Sociable (Latvian) Society and Evangelical Lutheran Congregation. The research uses the collection of Tukums Museum and Libraries, and documents of the Latvian National Archives.